Comunicación no verbal durante la pandemia por la enfermedad de Coronavirus 2019 - Borja-Villanueva, César Andrés (2021)
The present study aimed to explore the characteristics of non-verbal communication during the coronavirus disease pandemic. Materials and Methods: An exploratory cross-sectional study was carried out in a population between 18 and 65 years old from Lima. The participants were selected by convenience sampling. A virtual questionnaire of 9 questions was applied on non-verbal communication variable and 3 questions about parentage data. Results: A total of 391 individuals were included. The results of the kinesic dimension indicate that the frequency of gestures and facial expressions (51.9%) and the width of the smile (42.7%) did not change during the pandemic. In the proxemic dimension, it was found that the majority considerably decreased the frequency of kissing on the cheek (74.2%), kissing on the lips (56%) and the intensity of kissing (54.5%). For the paralinguistic dimension, the volume of the voice did not change in most individuals (52.4%) and nor did the speed of speech or articulation of words (57.5%). Conclusions: The COVID-19 pandemic has produced changes in non-verbal communication, the most important being a reduction in the frequency and intensity of kissing on the lips and cheek, while the volume and speed of the voice did not vary greatly. Neither have gestures, expressions and smiling undergone major changes.